Shrink-Swell Soils of Rice-based Cropping System of Old Deltaic Plains, Tamil Nadu: Their Characterization and Classification - M. Lalitha (Journal of the Indian Society of Soil Science, 2023)
Two typifying pedons representing the Olimathi and Naramangalam series in rice-growing shrink-swell soils of the old deltaic plains of Tamil Nadu were characterized for their physical, chemical, and nutrient properties. The soils were very deep (>200 cm), dark colored (10YR3/2 to 2.5Y5/2), having in-filled thin discontinuous sandy streaks across the depth. The clay content was high (37.7 to 54.1%), and the soil water retention at 33 kPa and 1500 kPa pressure varied from 23.5 to 47.6 and 12.7 to 25.5%, respectively. Soil organic carbon, DTPA extractable copper, iron and zinc content were decreased with depth. The COLE value of the soils was high (0.09 to 0.17), and cation exchange capacity (CEC) ranged from 22.9 to 36.6 cmol(p+)kg-1 soil. The rice-growing areas of old deltaic plains with changing soil moisture status with the season and high base saturation favoured the formation of shrink-swell soils. Soils are classified into Typic Haplusterts (Olimathi series) and Sodic Haplusterts (Naramangalam series) based on soil taxonomy.